The long struggle of the Amazon employees - Boewe, Jörn; Schulten, Johannes (Brussels, 2017)
"For more than three years, including over 100 days on strike, Amazon’s employees in Germany have been fighting for a collective agreement. Although they haven’t won yet, their struggle is emblematic of low-wage workers taking on a global corporation. The conflict at Amazon has become a “laboratory of resistance,” where important lessons have been learned, not only with respect to resistance against low wages and precarious employment in Germany, but also for workers who are fighting back at Amazon’s other sites in Europe. Everywhere in Europe, Amazon takes an extremely anti-union stance, but trade union resistance is forming across the continent–in Poland, France, the UK, Spain, and elsewhere. Transnational networking of employees and dialogue about experiences in various countries are a vital precondition for a successful, cross-border fight. This study is the result of intensive research by the journalists Jörn Boewe and Johannes Schulten on Amazon’s corporate structures and about both the experiences of trade union resistance in Germany and the prospects for cross-border industrial action by Amazon employees. This research is based on, among other things, a series of interviews with Amazon strike activists and participation in a number of trade union meetings. ..."